(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Cucumber (Cucumis sativus L) is an important member of the Cucurbitaceae family. Production of healthy nursery is necessary for high-quality production of this crop in greenhouses and in fields. With the idea of minimizing the use of pesticides and mineral fertilizers to preserve soil quality, we investigated the effects of plant growth promoting bacteria (PGPB) on growth promotion and protection of cucumber plants from phytopathogenic fungi. The effects of Pseudomonas spp. strains with different antifungal activities and Bacillus sp. Q10 strain with PGP activity were tested on cucumber plants. Antagonistic activity of Pseudomonas spp. against the growth of several phytopathogenic fungi isolated from cucumber: F. acuminatum, B. cinerea and A. niger, was observed. The influences of overnight cultures, supernatants and heat-stable antifungal factors were tested on the phytopathogenic fungi in vitro. Pseudomonas sp. K35 and K24 strains were more effective than P. chlororaphis Q16 and Pseudomonas sp. K27, showing 70-80% of fungal growth inhibition regardless of culture or fraction applied. The good antagonists that belong to pseudomonads and Bacillus sp. Q10 strain were used as mixtures for estimation of plant growth and health promoting effects on cucumber plants. Growth dynamics differed depending on the applied strain of Pseudomonas sp. The M3 treatment (a mixture of Bacillus sp. Q10 and P. chlororaphis Q16) stimulated the initial phase of growth, while M4 (a mixture of Bacillus sp. Q10 and Pseudomonas sp. K24) resulted in the maximal height at the final measurement. Significant differences in leaf and plant weight (M4), and leaf weight (M5, containing K35 strain) were found after the treatments. No significant differences in chlorophyll and NBI level were observed in any of the tested combinations. The obtained results suggested that M3 was suitable for stimulation of the early phase of cucumber growth, while the mixtures M4 and M5 improved plant protection and stimulated the later phases of cucumber growth.